Cultural representation of music and performing arts in Johor Old Temple’s Parade of Deities in Malaysia - Lee, Soo Foon (2018)
Johor Old Temple’s Parade of Deities is an annual large-scale procession of the local Chinese communities in Johor Bahru that marks a difference from other folk parades by parading with deities of five different clans, and showcasing a vast array of Chinese folk performing arts all in one single event that lasts for five days. Literatures have illustrated the Parade as a symbol of communal vitality but the numerous performances played simultaneously that form the main body of the event are unmentioned. This study examines a possible way to categorise the seemingly eclectically arranged performances, and unveils the details of the huge expository of performing arts in the Parade. Applying Hall’s cultural representation coupled with Bohlman’s notion on music as representation, this study addresses how the many cultural symbols, signs and icons of different regional origin and of different forms are being arranged enabling the unusual co-existence of five clans and their deities in a single event. Besides, it also scrutinises the effect of representation of each performance genre in determining the roles music plays in the Parade as cultural texts. Results from long term observation from 2011 to 2015 and repeated search and gathering of information and views from publications and various stakeholders. A taxonomy is devised. It conceptualises performances involved in the Parade in subcategories of dances, instrumental ensembles with songs, and dialectal operas. Dance as a broad category could be approached as masked dance that carries ritual function like Lion Dance, Dragon dances and Big Head Dolls, and the non-masked genres, like Chinese Fan Dance, Martial Arts, Diabolo and Flagpole-waving. Instrumental genre consists of those inherited from ancestry and the locally created ensembles, and is a clear means of proclaiming clan identity. The extremely rare simultaneous staging of five dialectal operas provides a field for competing spirituality. Each opera has its own set of deities and ritual, and brings rich but complex connotations both in social meaning and artistry. The spirit of co-ruling among clans and the structural frames of “five clans-only” form the backbone of the Parade, of which spirituality is the dominant function and changes over time remain negligible. “Other-representation” is prioritised over “selfrepresentation” among the many performing troupes in the Parade of Deities. Music is needed more for its symbolic, representative nature rather than for music itself. The real social subjects of the Parade are first of all spirituality in relation to deityworship, then the proclamation of diaspora identity within a multi-ethnic and polarised nation. The Parade is a venue of sustaining cultural memory of the local Chinese, reflecting the paradoxical inter-clan relationship among them, and a testimony of struggle for social recognition.